Updates of Road Safety Status in Malaysia - Radin Sohadi, Radin Umar (2005)
Since the last decade, Malaysia has experienced a remarkable period of economic expansion and growth in population, economy, industrialization and motorization. The population increased from 19.5 to 25.6 million at an average growth rate of about 35 per year. During the same period, the total length of paved roads increased from 60,734 to about 71,814 kilometers while registered vehicles increased from 7,210,089 to 13,878,000 vehicles in 2004 (Table 1). Over a span of 10 years, ownership increased accordingly from 2.7 persons per vehicle in 1994 to 1.9 persons per vehicle in 2004, thought almost half are motorcyclists. The increase in population and motorization led to a consequent increase in the number of road traffic accidents. From 148,801 cases in 1994 (Table 1), the number doubled to a total of 326,817 cases in 2004. the number of facilities (death within 30 days after an accident however, increased at a much slower rate from 5,159 in 1994 to 6.223 in 2004. note that the upward trend of fatalities dropped in 1997 after consistently positive growth since 1986.